2021
DOI: 10.1111/ijlh.13754
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between leukocyte‐platelet aggregates and thrombosis in myeloproliferative neoplasms

Abstract: Introduction The impact of activated blood and endothelial cells on the thrombosis in myeloproliferative neoplasms (MPN) has not yet been clarified. We prospectively analyzed correlation between circulating leukocyte‐platelet aggregates and soluble selectins to thrombosis occurrence in MPN, in the context of standard and cardiovascular risk factors, and different clinical and biological characteristics. Methods Flow cytometric analysis of neutrophil‐platelet (Neu‐Plt) and monocyte‐platelet (Mo‐Plt) aggregates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Beyond paracrine mechanisms, platelets can also form aggregates with various leukocyte subtypes, such as neutrophils, monocytes, and T cells ( 11 , 14 , 15 ). Platelet-leukocyte aggregates have been suggested to drive vascular disease and may potentially represent a biomarker for thrombotic events ( 9 , 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…Beyond paracrine mechanisms, platelets can also form aggregates with various leukocyte subtypes, such as neutrophils, monocytes, and T cells ( 11 , 14 , 15 ). Platelet-leukocyte aggregates have been suggested to drive vascular disease and may potentially represent a biomarker for thrombotic events ( 9 , 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…The copyright holder for this preprint this version posted December 11, 2022. ; https://doi.org/10.1101/2022.12.08.519689 doi: bioRxiv preprint hemostasis, platelets also contribute to thromboinflammatory processes by directly interacting with leukocytes 11 . Elevated platelet-leukocyte aggregates has recently been found to be an independent risk factor for thrombosis occurrence in MPN; it suggested that platelets may be a mediator between thrombosis and inflammation [12][13][14] . However, current evaluation of risk of MPNassociated thrombosis only consider quantitative change in platelets, the qualitative differences of platelets in MPNs have not been systematically evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…Aside from its classical functions in hemostasis, platelets also contribute to thromboinflammatory processes by directly interacting with leukocytes (11). Elevated platelet-leukocyte aggregates (PLAs) have recently been found to be an independent risk factor for MPN-associated thrombosis, indicating that platelets could be a mediator between thrombosis and inflammation (12)(13)(14). While it is known that thrombotic risk in MPNs is not directly correlated with the platelet count, the factors mediating aberrant activation of platelets in MPNs have not been systematically evaluated.…”
Section: Introductionmentioning
confidence: 99%